(untitled) (Fiep Bulletin - online, 2025)
Introduction: In the contemporary educational scenario, the search for innovative and effective strategies to optimize the teaching and learning process has become a constant priority. In this context, Artificial Intelligence tools have emerged as a promising alternative for the inclusion of minorities. Objective: The aim of this work is to comprehensively explore the application of Artificial Intelligence-based technologies in the educational context for Deaf people. Methods: The research was conducted in three widely recognized databases: Scielo, Google Scholar and PubMed. The choice of these databases is justified by the relevance of their publications in the areas of education, technology and health, which ensures a robust set of studies related to the topic. Results: The results found reflect a scenario with many possibilities, but which still has a small number of practical applications. Conclusion: Technology in education is a topic that should become increasingly common and relevant, and with this, the discussion of this type of tool in the education of deaf people should also evolve and deepen in the coming years. Teachers must be prepared and ready to face the situations encountered in the classroom, showing themselves to be facilitators and mediators in the learning process of their students, thus reducing the obstacles and barriers encountered by deaf people.